GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 228533 species occurrences available in GBIF matching the query: TaxonKey: Polyporaceae. The dataset includes 228533 records from 307 constituent datasets: 54 records from Mycological collection of the National Museum. 16 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 49 records from Jordal. 13 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 653 records from University of Vienna, Institute for Botany - Herbarium WU. 22 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 1935 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 8 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 16 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1776 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 102 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 60 records from Bryophytes, fungi and lichens on dead wood. 312 records from Naturalis Biodiversity Center (NL) - Botany. 443 records from PlutoF platform observations. 1 records from SPSF - Herbário Dom Bento José Pickel. 936 records from Notes from the Mycology Herbarium, Oslo (O). 3 records from Fiocruz/CCFF - Coleção de Culturas de Fungos Filamentosos. 343 records from Cercle des mycologues de Montréal Fungarium (CMMF). 2 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2286 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 65 records from Herbario Pontificia Universidad Javeriana. 855 records from ICN - Herbário do Instituto de Ciências Naturais. 4842 records from URM - Herbário Pe. Camille Torrand. 28 records from Fongs d'Andorra. 2 records from SA Flora (BDBSA). 3 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 55 records from Ontario BioBlitz Species Records. 1723 records from BioFokus. 431 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 100 records from CESJ - Herbário Leopoldo Krieger. 6 records from HAMAB - Herbário Amapaense. 70314 records from Artdata. 127 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 42 records from MBM - Herbário do Museu Botânico Municipal. 87 records from International Collection of Microorganisms from Plants (ICMP). 3032 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 996 records from Fungus herbarium, UiB. 16 records from OHN. 497 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 654 records from Données ONF Faune-Flore-Fonge. 1 records from FCAB - Herbário Friburguense. 17 records from Tallinn Botanic Garden. 1 records from Herbarium areqvipense (HUSA). 1 records from Agaricomycotina species reveald by ITS / LSU sequencing. 7531 records from Australia's Virtual Herbarium. 1443 records from iNaturalist Research-grade Observations. 80 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 15 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 129 records from UFRN-Fungos - Herbário UFRN - Fungos. 180 records from Fungi Collection. 297 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 31 records from Estonian Museum of Natural History. 71 records from ALCB - Herbário Alexandre Leal Costa. 4841 records from Estonian University of Life Sciences. 2 records from Klasse 3a. 1 records from Kremmer Luch. 1079 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Landschaftsschutzgebiet Buchhorst 3. 2 records from Wasserwerkspark (Chemnitz). 1 records from WildesMoor bei Schwabstedt. 1 records from Gelände des Schulzentrums am Himmelsbarg. 10 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 1 records from Garten in Schmölln. 10 records from Pilzlehrwald. 2 records from Hoher Stein Kallenhardt. 2 records from Nachtaktiv im Ökogarten (Bad Waldsee). 1 records from Landschaftsschutzgebiet Buchhorst 4. 2 records from Tiere und Pflanzen am Pfannenbach. 1 records from Boimstorfer Sundern. 10 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 4 records from Bannwald Burghauser Forst. 8 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 2 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 6 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 2 records from Weinberg Reichersdorf. 1 records from Schulwald Marksuhl. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Aachtobel. 1 records from Bodenteicher Seewiesen. 1 records from Reusaer Wald. 128 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc).. 16 records from Biodiversity records from Ireland - general. 1839 records from Fungi field notes, Oslo (O). 3477 records from naturgucker. 2 records from Outer Hebrides Biological Recording Project - OHBRP Fungi, Lichens and Lower Plants Dataset - Outer Hebrides. 17 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 95 records from National Trust - Hatfield Forest species data held by The National Trust.. 223 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 5 records from Biosphärenpark Wienerwald - Pfaffstätten. 4 records from Eschlberg Thalhausen. 14 records from GEO-Hauptveranstaltung in "Wildtierland". 2 records from Schulgelände des Schulzentrums am Himmelsbarg. 10 records from Bayerische Donau - Leipheim. 4 records from Dornwanger Moos. 1 records from Bulau. 4 records from Donauinsel des BN bei Entau. 1 records from Schieferbrüche. 1 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 439 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 4 records from MfN - Fossil plants (Cenophytic). 5 records from Dutch Vegetation Database (LVD). 1 records from Flora Atlas N.T.. 3 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from NZ National Vegetation Survey occurrence data. 4 records from Rådgivende Biologer. 5207 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 3 records from NSG Hellbachtal. 1 records from Ober-Olmer Wald 09. 104 records from Mushroom (KIDR-MR). 115 records from The Fungal Collection at the Botanische Staatssammlung München. 58 records from IBF Monitoring of Fungi. 166 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 2 records from Tropicos Specimen Data. 1 records from Natural History Museum (London) Collection Specimens. 620 records from Mycology herbarium, NTNU University Museum. 655 records from Hongos del estado de Veracruz. 6 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 46 records from Ireland's BioBlitz. 6 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 262 records from Fungal Collection of Natural History Museum and Institute, Chiba. 268 records from Ibaraki Nature Museum, Fungi collection. 621 records from Fungi on beech (Fagus sylvatica) wood, Halland, Sweden. 5 records from ARKO. 1876 records from Field Museum of Natural History (Botany) Fungi Collection. 255 records from CEPEC-Fungi - Coleção Micológica do CEPEC. 63 records from DSMZ Collection of Filamentous Fungi and Yeasts. 394 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 5 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from WA. 1 records from ANTARCTIC PLANT DATABASE. 380 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 605 records from BCCM/MUCL - (Agro)Industrial Fungi and Yeasts Collection. 115 records from CABI Bioscience Genetic Resource Collection. 783 records from CABI Bioscience Fungus Collection. 121 records from Herbarium (AMNH). 74 records from Real Jardin Botanico, Madrid: MA-Funhist. 72 records from Dpto. de Botánica, Ecología y Fisiología Vegetal. Facultad de Ciencias. Universidad de Córdoba. Fungi-COFC. 14 records from Database on Forest Disturbances in Europe. 5 records from MICROBIS database. 1199 records from Fungi collection of Jyväskylä University Museum. 6 records from Plant in Baekdu Mountain (KIDR-PL). 260 records from Mushroom in North Korean (KIDR-MR). 1 records from Paleobiology Database. 4 records from Individual Sightings. 982 records from Botanical Museum, Copenhagen, Mycology Herbarium. 24323 records from Danish Mycological Society, fungal records database. 1629 records from Fungal Specimens collected by HabitatVision (Jacob Heilmann-Clausen). 142 records from Plants of Papua New Guinea. 6 records from Invertebrate Zoology Division, Yale Peabody Museum. 107 records from ATCC Fungi Collection Catalog. 149 records from CBS Filamentous Fungi Database. 54 records from DSMZ Fungi. 31 records from IFO Filamentous Fungi. 12 records from GEO Biodiversity Day. 1 records from Herbarium Berolinense. 49 records from Lichen Herbarium Berlin. 84 records from Pollichia Pilzherbar. 356 records from Banc de dades de biodiversitat de Catalunya-FungaCat. 68 records from Water Colours of Fungi by Fritz Wohlfarth at the Botanische Staatssammlung München. 18 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 52 records from USU-UTC Specimen Database. 2137 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 100 records from MycoKey - online photos. 151 records from Fungi specimens of Kawasaki Municipal Science Museum for Youth. 4073 records from Harvard University Herbaria. 181 records from Mushroom Collection in BCRC. 41 records from Staffordshire Ecological Record - SER Site-based Surveys. 4762 records from Slovenian Fungal Database - Boletus informaticus. 2 records from Micoteca da Universidade do Minho. 2 records from Überall ist Wunderland. 4 records from Danielsberg (Mölltal, Kärnten). 5 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from AKG-Gelände (Bensheim). 12 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 11 records from Gemeinde Sursee. 1 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 1 records from Schulhof Bühlschule Giengen. 6 records from Schlern - (Bozen). 8 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Schule Sulzbach (Oberegg). 4 records from Königstetten. 1 records from Stausee (Oberdigisheim/Meßstetten). 1 records from Wald und Wiese am Buchwald. 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 5 records from Philosophenwald und Wieseckaue in Gießen. 6 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 8 records from GEO-Hauptveranstaltung (Insel Vilm). 1 records from Wanderweg am Windebyer Noor (bei Eckernförde). 6 records from BUND - Dassower See (Lübeck/Dassow). 6 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1 records from Gurgltal (Tarrenz). 5 records from Heinersdorfer Sumpfwiese. 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 1 records from Bergbaufolgelandschaft am Muldestausee. 1 records from "Tre Pini" (Montebelluna, Italien). 1 records from Field Museum of Natural History (Botany) Bryophyte Collection. 2 records from Streuobstwiese Kugelberg (Ulm). 1 records from Lüner Holz (Lüneburg). 2 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1 records from Tiergarten Straubing. 6 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 1 records from Prophetensee Quickborn. 2 records from Himmelmoor. 4 records from Tag der Artenvielfalt. 2 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 695 records from Natural History Museum, University of Tartu. 355 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 260 records from Herbarium of Umeå University (UME). 11 records from Schwanheimer Wald. 4 records from Lustadter Wald .. 1 records from Kohlstattbrunnental. 35 records from Departamento de Investigación y Experiencias Forestales de Valonsadero de la Junta de Castilla y León: JCYL-Fungi. 26 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 101 records from EDIT - ATBI in Gemer area (Slovakia). 37 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 331 records from Gunma Museum of Natural History, Fungi Specimen. 564 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 6 records from Artenvielfalt am Schlern. 3 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 343 records from Biological and palaeontological collection and observation data MNHNL. 1 records from Botany Division, Yale Peabody Museum. 13 records from Tag der Artenvielfalt im Taubental. 135 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 574 records from Mycological Collection - University of Washington Herbarium (WTU). 3 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 64 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 284 records from Mushroom - Higher Fungi (KIDR-MR). 117 records from Fungi collection of the Botanical Museum of the University of Oulu. 3 records from Wetland Inventory (NV). 2 records from UPCB - Herbário do Departamento de Botânica. 17 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 4 records from Faun. 8 records from ARKO gamle edellauvtrær. 3 records from HURB - Herbário do Recôncavo da Bahia. 158 records from ArtenFinder. 522 records from Lund Botanical Museum (LD). 4 records from Fungi Collection in BCRC. 5 records from National Trust - Ickworth species data held by The National Trust.. 134 records from Genebank, National Institute of Agrobiological Sciences. 73 records from Geographically tagged INSDC sequences. 33 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 12971 records from Norwegian Species Observation Service. 2 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Mycology collection, Norwegian Forest and Landscape Institute. 439 records from Bernice P. Bishop Museum. 157 records from FURB - Herbário Dr. Roberto Miguel Klein. 167 records from Staffordshire Ecological Record - SER Species-based Surveys. 39 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from ECatSym: Electronic World Catalog of Symphyta. 32 records from UFACPZ - Herbário da Universidade Federal do Acre. 557 records from Royal Botanic Garden Edinburgh Herbarium (E). 69 records from All observations extracted from the Flora of Northumberland and Durham 1831. 719 records from Botany (UPS). 22 records from HAS - Herbário Alarich Rudolf Holger Schultz. 800 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 39 records from Estonian Nature Observations Database. 1 records from crsn_data. 479 records from UFPB - Herbário Lauro Pires Xavier - (JPB). 1064 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 12 records from Ájtte. 101 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 139 records from R - Herbário do Museu Nacional. 1769 records from Fungi collection of the University of Eastern Finland. 2 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 115 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 14 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 654 records from Données ONF Faune-Flore-FOnge. 67 records from New Zealand Biodiversity Recording Network. 1 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 5 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 293 records from Royal Ontario Museum Fungarium (TRTC). 9 records from Ecofact. 3571 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 176 records from Registros de hongos en áreas protegidas de la Argentina. 2 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 4 records from The Bergius Herbarium. 7937 records from Mycology herbarium, Oslo (O). 50 records from Occurrences in SinBIOTA. 11 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 1 records from Anymals+plants - Citizen Science Data. 274 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 3436 records from Fungi of Costa Rica (INBio). 371 records from HFSL-Fungos - Herbário Dr. Ary Tupinambá Penna Pinheiro - Fungos. 36 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 3254 records from New Zealand Fungal and Plant Disease Collection (PDD). 17 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 222 records from Fundación Miguel Lillo - Colección Criptogámica. 72 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 4 records from Geneva Herbarium – General Collection (G). 1 records from Instituto de Botánica Darwinion. 547 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1359 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 1 records from CPAP - Herbário CPAP. 6 records from ClassII-peroxidase-sequences_from_pure_cultures_from_HAI. 44 records from National Museum of Natural Science. 1 records from Herbarium specimens of Limoges university (LIMO). 1939 records from Fungi (S). 3 records from PACA-AGP - Herbarium Anchieta. 961 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 9546 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences